Emergence of competing magnetic interactions induced by Ge doping in the semiconductor FeGa3 (2016)
ABSTRACT: FeGa3 is an unusual intermetallic semiconductor that presents intriguing magnetic responses to the tuning of its electronic properties. When doped with Ge, the system evolves from diamagnetic to paramagnetic to ferromagnetic ground states that are not well understood. In thiswork,we have performed a joint theoretical and experimental study of FeGa3−xGex using density functional theory and magnetic susceptibility measurements. For low Ge concentrations we observe the formation of localized moments on some Fe atoms and, as the dopant concentration increases, a more delocalized magnetic behavior emerges. The magnetic configuration strongly depends on the dopant distribution, leading even to the appearance of antiferromagnetic interactions in certain configurations.